The effect of a cold beverage during an exercise session combining both strength and energy systems development training on core temperature and markers of performance - LaFata Danielle; Carlson-Phillips Amanda; Sims Stacy T; Russell Elizabeth M (Journal of the International Society of Sports Nutrition, 2012)
Abstract Background Although studies have investigated the effects of hydration on performance measures, few studies have investigated how the temperature of the ingested liquid affects performance and core temperature during an exercise session. The hypothesis of the present study was that cold water would improve thermoregulation and performance as measured by bench repetitions to fatigue, broad jump for force and power and total time to exhaustion for cardiovascular fitness Methods Forty-five, physically fit, adult males (30.28 ± 5.4 yr, 1.77 ± 7.8 m, 83.46 ± 11.5 kg; 13.7 ± 4.8 %BF; 49.8 ± 6.3 ml/kg/min V02) completed two 60-minute exercise sessions. Subjects consumed either COLD (4°C) or room temperature (RT) water (22°C) in randomized order. Core temperature was measured every 15 minutes throughout each trial using a digestible thermometer. Three performance tests were performed upon completion of the exercise session: bench press to fatigue, standing broad jump, and bicycle time to exhaustion Results Although both groups significantly increased their core temperature (p<0.001) over the course of the exercise session and presented a significant decline in hydration status (p<0.001), participants in the COLD water trial had a significantly (p=0.024) smaller rise in core temperature (0.83°) over the duration of the trial in comparison to RT (1.13°). The participants in the COLD water trial were able to delay their increase in core body temperature for at least 30 minutes, whereas participants in the RT trial increased body temperature from baseline after 15 minutes. There was no significant difference between the COLD or the RT trials in broad jump and TTE performance tests. Bench press showed a small, albeit significant (p=0.046), decrease in performance when drinking COLD Conclusion Drinking cold water can significantly mediate and delay the increase in core body temperature during an exercise session in a moderate climate with euhydrated subjects. The ingestion of COLD improved performance for 49% and 51% of the participants in the broad jump and TTE performance tests respectively, but did not reach statistical significance. Moreover, although minimal, subjects experienced a decrease in performance on the bench press during the COLD.